Feasibility and acceptability of an online intervention with therapeutic assistance for parents of children with autism spectrum disorder in Chile: a case study - Chavarri, Maria Angélica; Canário, Ana Catarina; Cruz, Orlanda (Revista de Investigación en Logopedia, 2026)
The Early Start Denver Model (ESDM) is a naturalistic developmental behavioral intervention (NDBI), with a new and free Spanish online resource for families and therapists. This study assessed the feasibility and acceptability of an online intervention using this ESDM-based online resource, while doing online group meetings with a therapist. The intervention was completed after 8 group meetings, where they gathered with a therapist to clarify questions, present new topics, and share their experiences. The study evaluated satisfaction with the intervention, engagement, and use of naturalistic strategies in mother-child interaction, and mothers’ perceptions of changes in their child. Five autistic children under 40 months and their mothers participated. Mother-child behaviors were analyzed before and after the program through video recordings, while satisfaction and personal perceptions were analyzed with online surveys and semi-structured interviews. All participants completed the program and reported high satisfaction with the contents and meetings. They noted improvements in their use of naturalistic strategies and in engagement during interactions. Mothers felt more involved and observed positive changes in their children’s attention and communication. There were noted small changes in the mother-child interactions even after such a brief intervention. Online and short interventions can ease burdened healthcare systems, providing cost-effective family support. This is a first experience using this evidence-based resource in this country.